Evaluation of the BICGSTAB(l) algorithm for the finite-element - Topsakal, Erdem (IEEE Antennas & propagation magazine.)
We discuss the application of non-stationary Krylov-subspace-based iterative solvers to linear systems resulting from the application of the finite-element/boundary-integral method. A fairly new conjugate-gradient-based solver, BICGSTAB(l) is further described. The performance of several solvers is tested on a linearly tapered slot antenna (LTSA). Results showing the convergence characteristics and memory requirements are also given.